Eco-City-Based Sustainable Settlement Planning In Bengkayang New City Area - Weni Dewi Utami; Nunik Hasriyanti; Crysilla Tiara Vanziru (Jurnal Syntax Transformation, 2023)
The inability of a city to the pressure of increasing activity in urban areas which has encouraged the expansion of development into suburban areas is a phenomenon that often occurs in major urban centers. With the development of a new area, it can be a solution to solving urban problems, expanding the availability of housing and infrastructure, and reducing disparities between the main city and suburban areas. The development of a new city, in addition to physically changing the suburban area, can also have a socio-economic impact on the people, as a challenge to fulfill the welfare of the urban housing phenomenon. Bengkayang Regency is one of the developing districts. As one of the border frontier cities in West Kalimantan Province, Indonesia, Bengkayang is the main border gate between Indonesia and neighboring Malaysia and Brunei Darussalam. The great potential of Bengkayang Regency has not been supported by adequate urban planning and arrangement, which can reflect unique regional characteristics (local wisdom). The local government has established a policy regarding the development of a new city in Bengkayang, which is located in the Bumi Sebalo Village. This study aims to carry out sustainable settlement planning in the New City Area of Bengkayang based on Eco-City. Determination of the location based on the new Bengkayang city master plan data, namely in the sub BWP housing and green open space, with a descriptive qualitative analysis method. Settlement planning carried out includes aspects of housing, area support facilities and public green open spaces. The direction for housing arrangement uses a balanced residential concept, with a cluster system without guardrails, a grid pattern following the contours and condition of the land, pedestrian-friendly, and utilizing natural potential in the form of river flows as public open space areas and jogging tracks. Commercial facilities as supporting areas are placed on main road access with more strategic functions. Public green open space as a means of socializing and recreation on a city scale, how many sub-BWP green open spaces are equipped with urban forests as bearers of ecological functions, playgrounds, water fountains, amphitheater, street vendor areas to support the local community's economy, festival market areas as well as several tourist and cultural attractions as support activity.